Estudo da álcali-ativação de pó de blocos cerâmicos com cal hidratada - Macioski, Gustavo (2017)
Ceramic materials from bricks and tiles present in construction waste are considered contaminants in the production of recycled aggregates, as they have a low compressive and impact strength, as well as high porosity. These characteristics make mortars and concretes produced with mixed recycled aggregates have low compressive strength and high water absorption due to the porosity of the recycled aggregates. As an alternative to the technological use of this type of material, the ceramic has been studied as an alkali-activation raw material, either by direct combination with hydrated lime or as an addition to Portland cement (pozzolan reaction). The aim of this work is to study the alkali-activation of ceramic bricks powder with hydrated lime, aiming binding properties. For this, the study was carried out in three stages: evaluation of the reactivity of the ceramic bricks powder as a function of the burning temperature; evaluation of the reactivity of the ceramic bricks powder as a function of the particle distribution; and the evaluation of the alkaliactivation reaction kinetics as a function of the SiO2/CaO molar ratio, as well as the cure method. From the results obtained, it was observed that the reactivity of the ceramic bricks powder is influenced by the burning temperature of the clay and the size of the particles. The commercial ceramic bricks did not meet the physical requirements to be classified as pozzolan, obtaining in the Chapelle test the value of 305 mg of Ca(OH)2 fixed by gram of pozzolan and 5.5 MPa of compressive strength with lime in the IAP test. The addition of Ca(OH)2 in the ceramic bricks powder whose SiO2/CaO molar ratio was 2.75 gave the highest compressive strength when cured at 77 °C and 90% of relative humidity, reaching 8.5 MPa at 28 days. In the course of the alkali-activation reaction of the ceramic bricks powder, it was observed low hydration heat and accelerated portlandite consumption. At the end of the reaction it was possible to determine calcium silicate and aluminum silicate hydrated phases by X-ray diffraction and reticular morphologies by the scanning electron microscopy.